From learning to labour to custody for the precariat. (December 2018) - Sernhede, Ove
The globally reported riots in the poor high-rise suburbs of Sweden's metropolitan districts in 2013 were stark manifestations of the increased social and economic inequality of the past 30 years. Large groups of young adults acted out their unarticulated claims for social justice. In the light of the riots, it is relevant to ask whether any trace of resistance or protest can be found in the compulsory school where the young people from these neighbourhoods spend their days. The ethnography sampled for the article comes from two public schools in two poor, multi-ethnic, high-rise neighbourhoods on the outskirts of Gothenburg. The article argues that the theoretical and methodological concepts and perspectives developed by Willis still is of crucial importance to any investigation aimed at understanding the presence or absence of resistance in contemporary Swedish schools.